Information Analysis of the dissemination of the plastic arts in the galleries of Tabasco: El Jaguar Despertado Art Gallery: A place full of history and art - Pérez Montero, Donovan Javier (Cinzontle, 2024)
The objective of this study is to analyze the function that art galleries have in thedissemination of the plastic arts in the state of Tabasco, for this the study was usedcase from the gallery The Awakened Jaguar. The methodology used wasdocumentary research, as well as non-participant observation, taking asunit of analysis the information collected in various documents and the work offield made. Among the findings, it stands out that this gallery as an instancegovernmental public does exercise the function of being an accessible space forTabasco artists who seek to promote themselves and actively participate in theart market as a means of employment. They have a veryreduced because they are only limited to institutional virtual networks, which preventsthe reach is massive and they can become art-consuming public. HEsuggests that they diversify their promotion mechanisms and create otheractivities that incite the interest and assistance of society.